On reflexive and participatory approaches in digital preservation today. Interview with Samantha Lutz - Harrower, Natalie (Hamburger Journal für Kulturanthropologie (HJK), 2018)
Digitisation brings new demands and new challenges to the realm of cultural heritage, particularly around voice and preservation. Natalie Harrower is Director of the Digital Repository of Ireland (DRI), a national digital repository for archiving, preserving and providing access to Ireland’s cultural heritage, humanities and social sciences data. In the interview, Natalie Harrower examines current developments in digital preservation from a practical perspective, offering concrete examples that range from technical and legal challenges and participatory memory practices to future challenges of digital preservation such as creative practices of reuses, economies of sharing cultural heritage and preservation of digitally-born materials. Against this backdrop, she addresses ethical issues and the question of cultural sustainability, spanning the poles of remembering and forgetting and diverging preservation strategies in today’s digital universe.